Florence Nightingale : an introduction to her life and family - Nightingale, Florence, 1820-1910 (Nightingale, Florence, 1820-1910. Collected works of Florence Nightingale, 2001)
Florence Nightingale: An Introduction to Her Life and Family introduces the Collected Works by giving an overview of Nightingale's life and the faith that guided it and by outlining the main social reform concerns on which she worked from her call to service at age sixteen to old age. This volume reports correspondence (selected from the thousands of surviving letters) with her mother, father and sister and a wide extended family. There is material on Nightingale's domestic arrangements, from recipes, cat care and relations with servants to her contributions to charities, church and social reform causes. Much new and original material comes to light, and a remarkably different portrait of Nightingale, one with a more nuanced view of her family relationships, emerges.